OPTIMIZATION OF UMKM CRACKERS INTEGRATING LABELING AND PACKAGING - Purwanti, Yanik; Afiati, Nanda Nurul; Aldiantofas, Rizky Dwi; Handayani, Afikha Raya; Pranata, Aqshal Firdaus Satya (Antis-publisher, 2024)
General background: UMKM (Micro, Small, and Medium Enterprises) play a crucial role in the economic development of local communities, with packaging and labeling being key elements that can significantly influence consumer behavior and market expansion. Specific background: Many small businesses, such as UMKM Kerupuk Ibu Badroh in Putat Village, lack proper packaging and labeling, which hinders their competitiveness in the market. Knowledge gap: Despite the importance of these factors, there is limited research on how improving packaging and labeling can enhance the market presence of rural MSMEs. Aims: This study aims to increase the purchasing and selling power of UMKM Kerupuk Ibu Badroh by improving labeling and packaging elements through a qualitative, descriptive approach. Results: The implementation of modern and informative labels and functional packaging resulted in a significant increase in consumer confidence, product appeal, and sales. Novelty: This study highlights the transformative impact of packaging and labeling on the competitiveness of rural MSMEs, demonstrating how such improvements can lead to market expansion and enhanced product quality. Implications: The findings suggest that a strategic integration of modern packaging and labeling can strengthen MSME positions in the market, contributing to business sustainability and professionalization.